Polimorfizm izoenzymów i wzrost wybranych pochodzeń świerka pospolitego [Picea abies (L.) Karst.] doświadczenia IPTNS-IUFRO 1964/68 w Krynicy - Masternak, Katarzyna; Sabor, Janusz; Zielińska, Monika (Leśne Prace Badawcze, 2011)
To test the relationship between the genetic structure and growth parameters of thirty Norway spruce [ Picea abies (L.) Karst.] provenances growing on the IPTNS-IUFRO 1964/68 experimental plot in Krynica, the height and diameter at breast height (DBH) of 45-year-old spruce trees were measured. There was a significant effect of origin on both parameters, and correlation coefficients calculated for the relationship between growth characteristics and altitude of mother stands were negative and gave r = -0.16 for height and r = -0.15 for diameter at breast height. The parameters indicating the genetic diversity of thirty Norway spruce provenances, including the mean number of alleles per locus, effective number of alleles per locus and observed heterozygosity, were similar to the values obtained for the whole range of Norway spruce across Europe and were equal to 1.41, 1.16 and 0.115, respectively. There were no differences between the genetic variation of spruce provenances from the IPTNS-IUFRO 1964/68 experimental plot in Krynica and the areas from which seeds were obtained. There was a significant negative relationship between heterozygosity and altitude of mother stands (r = -0.33).